An Analysis of Teacher Talk and Student Talk in English Classroom Interaction Using FLINT System at The Ninth Grade of SMP Negeri 3 Hulu Sungai Tengah - Septiana Astutie (UMBanjarmasin, 2020)
The research aims to describe the types of teacher talk and student talk found in the English classroominteraction using Foreign Language Interaction (FLINT) system. This research was conducted in SMPNegeri 3 Hulu Sungai Tengah and involves two class of the ninth grade. This research used descriptivequalitative design. The data were obtained with observation and recording of interaction between teacherand students during teaching and learning activity. The data on the recording converted into transcript andanalyzed with selecting, focusing and summarizing which fit to teacher talk and student talk categories. Thefindings showed teacher and students were using the categories of talk which mentioned in FLINT system.The result revealed the teacher mostly used asking question category. Then, the teacher continued to usingtalk categories such as, giving information, giving direction, praising or encouraging, criticizing studentsbehavior, using ideas of students and dealing with feelings. Meanwhile, students was giving their specificresponse and their open-ended response during learning activity. Based on the result, it can besummarized that teacher mostly using asking question to build and interaction in the classroom and thestudents always giving their response every time the teacher asking a question. Furthermore, somesuggestions formulates as: for the teacher, they should evaluating and developing their talk throughclassroom interaction. Then, for the future researcher, they can using this research as a references withcompleted data and extending research in English classroom interaction at different location.